Juridical Study of the Work Relations Between Doctors and Hospitals in the Implementation of Health Services - Maya, Felicia; Sarwo, Budi; Wibowo, Daniel Budi (Universitas Katolik Soegijapranata Semarang, 2023)
In principle, laws and regulations have regulated the working relationship between doctors and hospitals in the implementation of health services, but in the field it is often found that there are many models of legal relations between doctors in hospitals which, when examined more deeply, are found to be incompatible with existing legislation. In addition, the doctor's relationship with the hospital which is not stated in a clear agreement and legal relationship, often creates disagreements between hospital management and doctors, especially when there are demands for compensation or other responsibilities demanded by third parties for the services of doctors at home. sick. This study raises issues that are also the purpose of writing, namely the legal basis for the occurrence of work agreements and the implementation of legal relationships that occur between doctors and hospitals as well as patterns of effective legal responsibility for doctors in hospitals. This research includes empirical legal research that is descriptive analytical using primary and secondary data types. The analysis is carried out by connecting relevant theories, namely applicable laws and regulations, hospital legal theories and positive law enforcement practices related to the problems in the research. From the results of the study, it was concluded that the working relationship between doctors and hospitals was bound in a work agreement which contained the legal responsibilities of each party.